Load Sensor Instability and Optimization of MEMS-based Tensile Testing Devices - Pantano, Maria F.; Calusi, Benedetta; Mazzolai, Barbara; Espinosa, Horacio D.; Pugno, Nicola M. (Frontiers in Materials, 2019)
MEMS-based tensile testing platforms are very powerful tools for the mechanical characterization of nanoscale materials, as they allow for testing of micro/nano-sized components in situ electron microscopes. In a typical configuration, they consist of an actuator, to deliver force/displacement, and a load sensor, which is connected to the sample like springs in series. Such configuration, while providing a high resolution force measurement, can cause the onset of instability phenomena, which can later compromise the test validity. In the present paper such phenomena are quantitatively discussed through the development of an analytical model, which allows to find a relationship between the rise of instability and the sensor stiffness, which is the key parameter to be optimized.